Reliability and Validity Of The DSM-5 Level 2 Depression Scale- Turkish Version (Child Form for 11-17 years and Parent Form for 6-17 Years) - Sermin Yalin-Sapmaz; Nefize Yalin; Canem Kavurma; Bengisu Uzel Tanriverdi; Signem Oztekin; Ertugrrul Koroglu; Omer Aydemir (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Introduction: This study aimed to assess the reliability and validity of the Turkish version of The DSM-5 Level 2 Depression Scale. Method: The study group included a case group that consisted of a clinical sample diagnosed with depressive disorder that continued treatment in a child and adolescent psychiatry unit and a community sample. The study was carried out with 218 children and 160 parents. The Child Depression Inventory and Strengths and Difficulties Questionnaire- Parent Form were used along with the DSM-5 Level 2 Depression Scale for assessment. Results: In reliability analyses, Cronbach alpha internal consistency coefficient was found to be very high for child and parent forms (0.965/0.952). Item- total score correlation coefficients are high and very high, respectively and were found to be consistent with the original structure of the scale (0.725 and 0.864 for child form- 0.644 and 0.839 for parent form) As for concurrent validity, child form had a high correlation with the Childrens Depression Inventory while parent form had a significant correlation with Strengths and Difficulties Questionnaire- Parent Form (r=0.853 p [JCBPR 2017; 6(1.000): 15-21]